Digitalization of the economy in the context of globalization and its impact on socio-cultural changes in society - Nevmatulina, K.А.; Nabiyev, Е.Н.; Shakeyev, C.C. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
The relevance of the article is due to the fact that the modern economy is entering a new innovative stage of development, and a person with his potential, knowledge, creative thinking and experience is gaining more and more importance. The study carried out by the authors confirmed the relevance and relevance of digitalization processes, which is due to the need and irreversibility of transformation in the digital economy, through the introduction of modern digital technologies, thanks to which the efficiency of the economy as a whole increases. To achieve this goal, the authors analyzed the main global trends in the 4.0 market, the positive aspects and risks for companies during the period of digital transformation, the impact of digitalization on all aspects of human life. As a result of the study, the authors determined the impact of global digitalization on the socio-cultural transformation of society, and identified some indicators of a digital society. Among them, one can designate the active use of the Internet of Things (smart technology, smart space and the concept of the development of a smart city), storage and processing of big data, the active introduction of automation and robotization, positive demographic changes, a networked society, greening, acceleration of technological and social changes, leading to transformation of the labor market.